Some breach of the Walles’ Rule and other peculiarities of the fauna in the Weddell Sea - Sirenko, B. I.; Smirnov, I. S. (Ukrainian Antarctic Journal, 2012)
According to the rule of de Candolle-Walles a species diversity decreases from low latitudes regions to high latitudes regions. However in the Weddell Sea the biodiversity of the fauna of some groups are approximately the same (Actiniaria, Mysidacea, Cumacea, Gastropoda, Bryozoa, Echinoidea) or more than this in the Magellan region (Spongia, Pycnogonida, Holothuroidea, Asteroidea, Ohpiuroidea, Ascidiacea). In spite of the rather high species diversity of bivalves in the Weddell Sea, communities where bivalves dominated (like in Arctic seas) practically are absent and average size of gastropods and bivalves is much less than in the Arctic Ocean. Moreover Reptantia from Decapoda crustacean is absent in the Weddell Sea. We will try to explain the reasons of the breach of the Walles rule of the fauna and will try to explain some other peculiarities of the Weddell Sea. For this purpose we will compare the fauna of some groups in the Magellan region and in the Weddell Sea (Table. Number of species of different genera the Magellan Region and in the Weddell Sea).